Novel combination strategy of high intensity focused ultrasound (HIFU) and checkpoint blockade boosted by bioinspired and oxygen-supplied nanoprobe for multimodal imaging-guided cancer therapy - Ying Zhou; Chen Cheng; Qi Wang; Min Zheng; Pan Li; Yang Zhou; Yuting Cao; Li Wan; Xun Guo; Xiaohong Lin; Rui Tang; Hongye He; et al. (Journal for ImmunoTherapy of Cancer)
Background High-intensity focused ultrasound (HIFU) has shown considerable promise in treating solid tumors, but its ultrasonic energy is easily attenuated, resulting in insufficient energy accumulation in the target area. Moreover, HIFU ablation alone may inevitably lead to the presence of residual tumors, which may cause tumor recurrence and metastasis. Here, we describe a synergistic regimen combining HIFU facilitation with immunomodulation based on a novel oxygen-carrying biomimetic perfluorocarbon nanoparticle (M@P-SOP) to stimulate immunogenic cell death in tumor cells while alleviating immune suppression tumor microenvironment.Methods M@P-SOP was prepared by double emulsion and film extrusion method. The anticancer and antimetastatic effects of M@P-SOP were evaluated on a preclinical transplanted 4T1 tumor model by combining HIFU and immunotherapy. Flow cytometry and immunofluorescence were used to clarify the potential mechanism of HIFU+M@P-SOP and their role in anti-programmed death ligand-1 (PD-L1) therapy.Results Guided by photoacoustic/MR/ultrasound (US) multimodal imaging, M@P-SOP was abundantly enriched in tumor, which greatly enhanced HIFU’s killing of tumor tissue in situ, induced stronger tumor immunogenic cell death, stimulated dendritic cell maturation and activated CD8+ T cells. At the same time, M@P-SOP released oxygen to alleviate the tumor hypoxic environment, repolarizing the protumor M2-type macrophages into antitumor M1-type. With concurrent anti-PD-L1 treatment, the antitumor immune response was further amplified to the whole body, and the growth of mimic distant tumor was effectively suppressed.Conclusions Our findings offer a highly promising HIFU synergist for effectively ameliorating acoustic and hypoxia environment, eventually inhibiting tumor growth and metastasis by stimulating host’s antitumor immunity under HIFU ablation, especially in synergizing with PD-L1 antibody immunotherapy.